Machine learning in clinical and epidemiological research: isn't it time for biostatisticians to work on it? (Epidemiology, Biostatistics, and Public Health, 2022)
In recent years, there has been a widespread cross-fertilization between Medical Statistics and Machine Learning (ML) techniques.